PENINGKATAN KUALITAS PENGELOLAAN KELASMELALUI MANAJEMEN DISPLAY KREATIF BAGIKELOMPOK KERJA GURU SD KECAMATAN PAKAL KOTA SURABAYA - Putri Rachmadyanti (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThe training aims to build motivation, understanding, and skills of elementary school teachers in designing, creating and managing creative classroom displays. The basis of this training is the number of teachers who do not understand the techniques and forms of management of creative classroom displays. The nature of the theme-based curriculum in 2013 which also allows the teacher to the creation of learning according to the theme, either through the material presented and design classes. The training was conducted by multi-method, allowing participants to get a challenge in following the activities. The results of the activities include various forms of class displays that show participants' enthusiasm in designing and creating creative class displays.Keywords: Classroom Management, Display, Elementary School